Single-cell transcriptomic characterization of microscopic colitis - Stefan Halvorsen; Molly Thomas; Mari Mino-Kenudson; Yuko Kinowaki; Kristin E. Burke; David Morgan; Kaia C. Miller; Katherine M. Williams; Jenny Gurung; Jessica McGoldrick; Megan Hopton; Brooke Hoppe; et al. (Nature Communications)
Abstract Microscopic colitis (MC) is a chronic inflammatory disease of the large intestine and a common cause of chronic diarrhea in older adults. Here, we use single-cell RNA sequencing analysis of colonic mucosal tissue to build a cellular and molecular model for MC. Our results show that in MC, there is a substantial expansion of tissue CD8+ T cells, likely arising from local expansion following T cell receptor engagement. Within the T cell compartment, MC is characterized by a shift in CD8 tissue-resident memory T cells towards a highly cytotoxic and inflammatory phenotype and expansion of CD4+ T regulatory cells. These results provide insight into inflammatory cytokines shaping MC pathogenesis and highlight notable similarities and differences with other immune-mediated intestinal diseases, including a common upregulation of IL26 and an MC-specific upregulation of IL10. These data help identify targets against enteric T cell subsets as an effective strategy for treatment of MC.